Numbers : arithmetic and computation - Mallik, A. K. (Asok Kumar), 1947-; Das, Amit Kumar ([Place of publication not identified] : CRC Press, 2022)
This book contains a number of elementary ideas on numbers, their representations, interesting arithmetical problems and their analytical solutions, fundamentals of computers and programming plus programming solutions as an alternative to the analytical solutions and much more. Spanning seven chapters, this book, while keeping its lucid storytelling verve, describes integers, real numbers and numerous interesting properties and historical references; followed by a good collection of arithmetic problems and their analytical solutions.
1. Introduction 2. Integers 3. Real Numbers 4. Problems 5. Solutions 6. Computer and programming fundamentals 7. Programming Solutions A. Brahmagupta's Equation B. Bernoulli Numbers C. Unit Fractions D. Pattern in Decimal Representation E. Platonic Solids F. Conversion table, Boolean Algebra rules, Floating Point Format etc. G. Your own Library, command line parameters and dealing with big numbers
OCLC-licensed vendor bibliographic record.
Keywords: Numeration; Mathematics; MATHEMATICS -- Number Theory; MATHEMATICS -- Arithmetic; MATHEMATICS / Arithmetic